Effect of propellant composition to the temperature sensitivity of composite propellant - Amir, Aziz; R., Mamat; Amin, Makeen; Wan Khairuddin, Wan Ali (IOP Publishing, 2012)
The propellant composition is one of several parameter that influencing the temperature sensitivity of composite propellant. In this paper, experimental investigation of temperature sensitivity in burning rate of composite propellant was conducted. Four sets of different propellant compositions had been prepared with the combination of ammonium perchlorate (AP) as an oxidizer, aluminum (Al) as fuel and hydroxy-terminated polybutadiene (HTPB) as fuel and binder. For each mixture, HTPB binder was fixed at 15% and cured with isophorone diisocyanate (IPDI). By varying AP and Al, the effect of oxidizer- fuel mixture ratio (O/F) on the whole propellant can be determined. The propellant strands were manufactured using compression molded method and burnt in a strand burner using wire technique over a range of pressure from 1 atm to 31 atm. The results obtained shows that the temperature sensitivity, a, increases with increasing O/F. Propellant p80 which has O/F ratio of 80/20 gives the highest value of temperature sensitivity which is 1.687. The results shows that the propellant composition has significant effect on the temperature sensitivity of composite propellant.